Reactive Infectious Mucocutaneous Eruption with Extensive Cutaneous Involvement - Zeynoire Anderson; Audrey Fotouhi; Starling Tolliver; Darius Mehregan (Clinical Dermatology Review, 2024)
Recently, there has been discussion to reclassify pediatric Stevens–Johnson syndrome/toxic epidermal necrolysis (SJS/TEN) as drug-induced epidermal necrolysis (DEN), separating it from infectious etiologies and redefining pediatric mucocutaneous eruptions as either reactive infectious mucocutaneous eruption (RIME) or DEN. In this report, we describe a previously healthy 4-year-old girl with rapidly progressive mucocutaneous blistering involving four mucosal membranes and 37.5% of total body surface area (BSA) following a prodromal rhinovirus and enterovirus infection. The symptoms occurred in the absence of an inciting medication and improved with only supportive care. This case illustrates a rare occurrence of RIME with TEN-like BSA involvement, prompting a review of the literature exploring the relationship between BSA involvement in RIME and its influence on patient outcomes. Findings support the proposed reclassification of SJS/TEN as DEN and postinfectious mucocutaneous eruptions as RIME.